A comparison of self-reports and electrodermal activity as indicators of mathematics state anxiety.: An application of the control-value theory - Strohmaier, Anselm Robert; Schiepe-Tiska, Anja; Reiss, Kristina M. (Frontline Learning Research, 2020)
In the present study with 86 undergraduate students, we related trait Mathematics Anxiety (MA) with two indicators of state anxiety: self-reported state anxiety and electrodermal activity (EDA). Extending existing research, we included appraisals of control and perceived value in hierarchical multiple regression analyses in accordance with the control-value theory of achievement emotions (Pekrun, 2006). Results showed that trait MA predicted self-reported state anxiety, while no additional variance was explained by including control and value. In contrast, we found no significant relation between trait MA and physiological state anxiety, but a significant, negative three-way interaction effect with control and value. Regression coefficients indicated that trait MA predicted physiological state anxiety, but only in the presence of negative perceived control and positive perceived value. Thus, our results support the control-value theory for physiological state anxiety, but not for self-reports. They emphasize the need to distinguish between trait and state MA, the advantages of adopting the control-value theory, and the benefits of using EDA recording as a supplemental assessment method for state anxiety.